Comparative analysis of dehydration techniques on phytochemical and antibacterial properties on pink and purple flowers impatiens walleriana - Tan, Suat Hian; Sin, Phin Yin; Ros Azlinawati, Ramli; Mohd Hairul, Ab. Rahim; Nyuk, Ling Ma (AIP Publishing, 2025)
Impatiens walleriana is an ornamental plant known for its rich antioxidant and antibacterial properties. These objectives of this study were to elucidate the impacts of various dehydration treatments (microwave, oven-, and conventional air-drying) on the antioxidant compounds of the pink and purple flower I. walleriana. Furthermore, the antibacterial properties of microwave-dried leaf extract against selected Gram-positive and Gram-negative bacterial strains were also tested. The results demonstrated that dehydration techniques significantly affected (p<0.05) the phenolic content, with the total phenolic content ranking in descending order: microwave drying > oven drying > conventional air drying. Leaf extracts had the highest total flavonoid content compared to stem extracts. Notably, the pink flower variety exhibited higher flavonoid content (0.528-0.541 mg QE/100g) than the purple variety, likely due to petal color variation. Microwave-dried leaf extracts were evaluated for antibacterial activity using the disc diffusion method. Both pink and purple flower varieties demonstrated inhibition of Gram-positive and Gram-negative bacteria, with the pink flower showing greater antibacterial effects. Both flower types were particularly effective against Escherichia coli and less against Pseudomonas aeruginosa. The antibacterial activity of I. walleriana against E. coli was nearly twice as strong as that of synthetic antibiotics. In conclusion, I. walleriana, particularly when microwave-dried, is a potent source of natural antioxidants and antibacterial agents.